KITAB TADABBUR AL-QUR’AN KARYA BACHTIAR NASIR DALAM PERSPEKTIF EPISTEMOLOGI - Fathor Rosy (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2019)
This study aims to examine the epistemology of the tadabbur al-Qur’an by Bahctiar Nasir. This book can be said as the only work Ulama’ of Indonesian. The tadabbur al-Qur'an is almost rarely found in the works of Ulama and al-Qur’an experts, both classical and modern, the scholars more often use the term tafsir, whereas many are found in the text of the Quran is a command to “reflection” not interpret. This research is a library research and field research with a descriptive-analytical method to reveal the epistemology of tadabbur al-Qur’an by Bachtiar Nasir. The conclusions of this study, namely: first, the concept of tadabbur al-Qur’an by Bachtiar Nasir is not much different from the books of commentary in general, the difference is only the addition of reflection or tadabbur at the end of each interpretation of the verse. This tadabbur al-Qur’an book when referring to the 10 steps of the tadabbur concept cannot be categorized as a tadabbur al-Qur’an book because both the content and the systematic writing are not much different from other interpretations. Keyword: Reflection, Bachtiar Nasir, Tafsir, Epsitemology